‘A Witness in My Own Case’ : Victim–Survivors’ Views on the Criminal Justice Process in Iceland - Antonsdóttir, Hildur Fjóla (Feminist Legal Studies, 2018)
Arguments in favour of strengthening the rights of victim–survivors in the criminal justice process have largely been made within the framework of a human rights perspective and with a view to meeting their procedural needs and minimising their experiences of secondary victimisation. In this article, however, I ask whether the prevalent legal arrangement, whereby victim–survivors are assigned the legal status of witnesses in criminal cases, with limited if any rights, is a just arrangement. In order to answer this question, the article draws on interviews with 35 victim–survivors of sexual violence in Iceland. The interviews are presented against the backdrop of Nordic legal thinking and are interpreted in the context of Nancy Fraser’s democratic theory of justice. On the basis of the findings, I argue that assigning complainants the role of witnesses constitutes a case of misframing that results in misrecognition throughout the criminal justice process.